Isolation, Identification and Antibiotic Susceptibility Patterns of Listeria Monocytogens from Pregnant Women - Jha, Brajesh Kumar; Adhikari, Neetu; Rajkumari, Sanjhana (Journal of College of Medical Sciences-Nepal, 2021)
Introduction The present study is made to determine the prevalence rate, isolation, identification and antibiotic susceptibility pattern of L. monocytogens isolated from pregnant women. This research not only guides to the clinician for treatment but also help laboratory worker to monitor susceptibility pattern among the Listeria species. Methods The samples were collected from Gynecology department from January 2017 to December 2019 and processed in the Department of Microbiology at College of Medical Sciences, Bharatpur Nepal. Two hundred thirty four antenatal mothers having age between 17 and 39 years of gestation period between 7th weeks and 36th weeks patient with a flue like sign and symptoms were screened for L. monocytogens. Bacterial isolation identification and antibiotic sensitivity tests were done as per standard microbiological guidelines. Results In this present research, the prevalence of L. monocytogens was found 39/234 (16.7%), where high rate of Listeria infection was found 21(53.1%) among the patients of age between 25 and 32 who were mostly from urban area. We found eating meat 38(97.4%) and fish 39(100.0%), non-pasteurized simple boiled milk 39(100.0%) and vegetables like salad eater 32(82.1%) has highest rate of listeriosis. The results showed most of the listeriosis were occurring in a 3rd trimester 17(43.6%) compared with the 2nd and 1st trimester. Overall, the antibiotics resistance pattern found low in L. monocytogens. This investigation also showed less resistance in erythromycin 9(23.1%), ciprofloxacin 8(20.5%), chloramphenicol 16(41.1%). The increased resistance pattern among Listeria species were found in penicillin 31(79.5%), cotrimoxazole 20(51.3%), amoxicillin 21(55.1%) and vancomycin 29(74.4%). Conclusions It is very important to consider listeriosis in a clinical practice now a day. Maternal Listeriosis should be considered in all age group of pregnant women. Regular surveillance of antibiotic susceptibility test is very much important for clinician to select best medicine to treat different cases of listeriosis.